“Selling Blood, Reading Pain”: Indonesian Readers' Responses to Sacrifice and Black Humor in Yu Hua's Chronicle of a Blood Merchant - Elizabeth Irene Hartanto (Published by Confucius Institute UNS, 2026)
This study examines Indonesian readers' responses to sacrifice and black humor in Yu Hua's Chronicle of a Blood Merchant. The novel tells the story of Xu Sanguan, a poor peasant who sells his blood repeatedly to support his family. What makes this novel distinctive is its unique narrative tone: a blend of tragedy and dark humor, using qualitative thematic analysis of 35 reader reviews from Goodreads and online book blogs, this research focuses on two aspects: how Indonesian readers respond to Xu Sanguan's sacrifices; and how they experience the novel's black humor. The findings reveal three key patterns. First, Indonesian readers strongly empathize with Xu Sanguan's sacrifices, appreciating his transformation from a selfish young man to a devoted father. Second, readers consistently recognize and appreciate the novel's black humor, describing their experience as